1994
DOI: 10.1002/app.1994.070511010
|View full text |Cite
|
Sign up to set email alerts
|

Calcium alginate gel fibers: Influence of alginate source and gel structure on fiber strength

Abstract: SYNOPSISThe low-deformation extension modulus was measured for Ca-alginate gel fibers prepared from alginates of different compositions and molecular weights. The modulus showed an increase with increasing molecular weight for alginates of the same composition and sequence parameters. Fibers prepared with an inhomogeneous polymer concentration profile showed higher moduli than did fibers with a homogeneous polymer concentration profile. The higher modulus observed for fibers prepared from an alginate with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Although the alginate concentration could have been further increased in the emulsion beads, this may have hindered insulin diffusion based on its viscosity radius of 1.3 nm 17. The bead rupture force was similar between the 5% emulsion and 1.5% extrusion beads, which can be explained by the higher strength of beads with higher gel gradients 31. The peak bursting force of capsules being used in human clinical trials has been reported to be as low at 8.8 mN 32.…”
Section: Discussionmentioning
confidence: 72%
“…Although the alginate concentration could have been further increased in the emulsion beads, this may have hindered insulin diffusion based on its viscosity radius of 1.3 nm 17. The bead rupture force was similar between the 5% emulsion and 1.5% extrusion beads, which can be explained by the higher strength of beads with higher gel gradients 31. The peak bursting force of capsules being used in human clinical trials has been reported to be as low at 8.8 mN 32.…”
Section: Discussionmentioning
confidence: 72%
“…It is the monovalent salt form of alginic acid comprising 1,4-linked b-D-mannuronic (M) and a-L-guluronic acid (G) units [19]. Alginate is a water-soluble polymer and forms gel in the presence of certain bivalent cation such as Ca 2þ through ion exchange [20].…”
Section: Introductionmentioning
confidence: 99%
“…SA is one of the most promising materials to achieve this goal. SA is an abundant linear polysaccharide obtained from marine brown algae, a biodegradable biopolymer and the simplest fundamental unit of SA is related to cellulose and the structural configuration is better represented by (1,4)‐β‐ D ‐mannuronate and (1,3)‐α‐ L ‐guluronate residues 30. SA was chosen because of its structural features, with carboxylic groups in every repeating unit that has α and β configurations.…”
Section: Introductionmentioning
confidence: 99%